Strongly \(T_{k}{^{g^{*}}}\)-Spaces (Journal of Informatics and Mathematical Sciences, 2019)
In this paper, we introduce the spaces called Strongly-\(T_{0}{^{g^{*}}}\)-space, Strongly-\(T_{1}{^{g^{*}}}\)-space and Strongly-\(T_{2}{^{g^{*}}}\) in topological spaces. Also, we introduce Strongly \(g^{*}\)-symmetric and studied some of their properties.
Keywords: Strongly-\(T_{0}{^{g^{*}}}\)-space; Strongly-\(T_{1}{^{g^{*}}}\)-space and Strongly-\(T_{2}{^{g^{*}}}\)